DUODENAL LYMPHANGIECTASIAS - THE FIRST SIGN OF PANCREATIC ADENOCARCINOMA - Taveira, Filipe; Magalh es, José Paulo; Brito, Daniel (Revista española de enfermedades digestivas, 2021)
A 41-year-old caucasian female, with past medical history of pituitary adenoma medicated with cabergoline, presented with worsening dyspepsia and unintentional weight loss of 5%. Physical exam and laboratory results were unremarkable for pathological findings. Esophagogastroduodenoscopy revealed an oedematous and exuberant lymphangiectasia appearance in the duodenum, with no ulceration or suspected infiltration component (figure 1 - A/B). However, duodenal biopsies revealed infiltration by poorly differentiated carcinoma (figure 1 - C/D). In the meantime, infection and inflammatory/autoimmune causes were ruled out. A CT scan was performed revealing a thickened and enlarged pancreas with ill-defined limits and several intra-abdominal adenopathies, raising suspicion of pancreatic lymphoproliferative disease. EUS with FNB was performed with biopsy of the pancreas and one of the larger adenopathy. EUS also revealed an enlarged, non-nodular pancreas and a thickened duodenal wall. Mild ascites was detected. Both EUS-biopsies were concordant on the diagnosis of carcinoma with gastric or pancreatic-biliary origin, highly aggressive (Ki67>80%). Therefore, the diagnosis of pancreatic adenocarcinoma was assumed (cT4N1Mx). The patient is currently on palliative chemotherapy and remains paucisymptomatic.